Biopsychosocial repercussions of work and income generation in the life of Northe-âstern Brazilian women - doi:10.5020/18061230.2007.p68 - Cibelly Aliny Siqueira Lima Freitas; Fabiane do Amaral Gubert (Universidade de Fortaleza, 2012)
In the discussions about health promotion, this is conceived as quality of life, in which social and economic policies should act directly on determinant factors of the health-illnesses process, such as feeding, education, sanitation, work, income, leisure and access to goods and services. In this perspective, the aim of this study was to investigate the expectations of a group of women, inhabitants of Cachoeiro Community, a deprived locality of Northeast Brazil, on the professionalization possibilities, and to know the biopsychosocial repercussions of work-income generation, after a professionalizing action. The study consisted in an action in research, with a qualitative approach, based on the Theoretical Referential of Madeleine Leininger, with six local women, by means of interviews and the accomplishment of a course on carnauba straw handicraft, between May, 2005 and June, 2006. This study resulted from the participation of the researchers in a University Extension project, which favored a bigger interaction with the women of that place. During sociability it was observed that they claimed for a work that contributed to the increase of the family income and breached with the financial dependence on their spouses. It is perceived in this study the cultural factor as strongly influencing the lives of these women, in which abusive relations of power, perceived since infancy, became obstacles in matters related to health, education and in the work and income generation. At the end, the women of the Community were able to seize upon a handicraft technique that contributes for their recognition as citizens, interacting with greater knowledge and attitude in the settlement where they live.